A treatment process for UTG glass after chemical strengthening and a preparation process for UTG glass
By accurately controlling the cooling and soaking temperature and time of UTG glass and performing two soaking treatments, the problem of UTG glass being easily fragile after chemical strengthening is solved, and the product yield and production efficiency are improved.
Patent Information
- Application Number
- CN202411870660.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-08
AI Technical Summary
UTG glass is prone to fragmentation when soaked in water after chemical reinforcement, resulting in low product yield.
The cooling temperature of the chemically strengthened UTG glass, the soaking temperature after cooling and the soaking time were accurately controlled, and two soaking treatments were carried out. First, soak in water at 45 to 55°C for 5 to 25 minutes, and second, soak in water at ≤34°C for 5 to 15 minutes to remove surface residues and promote uniform distribution of internal stress.
It effectively reduces the fragmentation rate after chemical tempering of UTG glass after soaking in water, improves production efficiency, and promotes the release and uniform distribution of internal stress in the glass.
Smart Images

Figure CN119774866A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of UTG glass preparation, and in particular to a treatment process for UTG glass after chemical strengthening and a preparation process for UTG glass. Background Art
[0002] Ultra-thin flexible glass (UTG) is a glass material with flexible and bendable properties. Its thickness is less than 100 microns. Unlike traditional rigid glass, it can be bent arbitrarily under the action of external force without thermal processing. UTG glass has the characteristics of ultra-thinness, wear resistance, high temperature resistance, corrosion resistance, high strength, high light transmittance, bendability and good resilience, and has good application prospects in electronic screens and other fields.
[0003] At present, the preparation process of UTG glass mainly involves: chemically strengthening the original glass sheet and then directly soaking it in water. However, since the thickness of UTG glass is thinner than that of traditional glass, the existing preparation process easily causes the UTG glass to break after being soaked in water, and the product yield is not high. Summary of the invention
[0004] The purpose of the present application is to provide a treatment process for UTG glass after chemical strengthening and a preparation process for UTG glass, which aims to solve the problem that UTG glass is prone to fragmentation after chemical strengthening and soaking in water.
[0005] In the first aspect, the present application provides a treatment process for UTG glass after chemical strengthening, the treatment process comprising: cooling the chemically strengthened UTG glass to a preset temperature, and then performing a first immersion in water at a temperature of 45 to 55°C; wherein the first immersion time is 5 to 25 minutes; when the ambient temperature is 0 to 10°C, the preset temperature is 35 to 60°C; when the ambient temperature is 11 to 20°C, the preset temperature is 38 to 60°C; when the ambient temperature is 21 to 30°C, the preset temperature is 42 to 60°C; when the ambient temperature is 31 to 40°C, the preset temperature is 47 to 60°C.
[0006] According to different ambient temperatures, the present application precisely controls the cooling temperature of the chemically strengthened UTG glass, the soaking temperature after cooling, and the soaking time after cooling, so as to remove the salt bath or other chemicals that may remain on the surface of the UTG glass after chemical tempering by soaking in water, promote the release and uniform distribution of stress inside the glass, and effectively reduce the fragmentation rate of the chemically tempered UTG glass after soaking in water, thereby improving production efficiency.
[0007] In combination with the first aspect, in an optional embodiment of the present application, the first soaking time is 15 to 25 minutes.
[0008] In the above technical solution, the fragmentation rate of chemically tempered UTG glass after soaking in water can be further reduced, thereby improving production efficiency.
[0009] In combination with the first aspect, in an optional embodiment of the present application, the treatment process after chemical strengthening of the UTG glass further includes: performing a second immersion on the UTG glass after the first immersion in water with a temperature of ≤34°C.
[0010] In combination with the first aspect, in an optional embodiment of the present application, the second immersion time is 5 to 15 minutes.
[0011] In combination with the first aspect, in an optional embodiment of the present application, when the ambient temperature is 0-10°C, the temperature of the second immersion is 5-12°C.
[0012] In the above technical solution, the fragmentation rate of chemically tempered UTG glass after soaking in water can be further reduced, thereby improving production efficiency.
[0013] In combination with the first aspect, in an optional embodiment of the present application, when the ambient temperature is 11-20°C, the temperature of the second immersion is 7-18°C.
[0014] In the above technical solution, the fragmentation rate of chemically tempered UTG glass after soaking in water can be further reduced, thereby improving production efficiency.
[0015] In combination with the first aspect, in an optional embodiment of the present application, when the ambient temperature is 21-30°C, the temperature of the second immersion is 16-24°C.
[0016] In the above technical solution, the fragmentation rate of chemically tempered UTG glass after soaking in water can be further reduced, thereby improving production efficiency.
[0017] In combination with the first aspect, in an optional embodiment of the present application, when the ambient temperature is 31-40°C, the temperature of the second immersion is 23-34°C.
[0018] In the above technical solution, the fragmentation rate of chemically tempered UTG glass after soaking in water can be further reduced, thereby improving production efficiency.
[0019] In a second aspect, the present application provides a preparation process for UTG glass, the preparation process comprising: chemically strengthening a glass substrate, and then performing a treatment process for the UTG glass after chemical strengthening as provided in any one of the first aspects above.
[0020] The preparation process of the UTG glass provided in the present application adopts the treatment process of the UTG glass chemically strengthened provided in the first aspect above, which can promote the release and uniform distribution of internal stress of the glass, and at the same time effectively reduce the fragmentation rate of the UTG glass after chemical tempering and soaking in water, thereby improving production efficiency.
[0021] In combination with the second aspect, in an optional embodiment of the present application, the surface temperature of the chemically strengthened UTG glass is 115-125°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a process flow chart of the chemically strengthened UTG glass provided in this application. DETAILED DESCRIPTION
[0024] The main process of preparing UTG glass is to chemically strengthen the original glass and then soak it in water. However, since the thickness of UTG glass is thinner than that of traditional glass, the existing preparation process easily causes the UTG glass to break after being soaked in water, and the product yield is not high.
[0025] The inventors have found through research that, by controlling the cooling temperature of the chemically strengthened UTG glass, the soaking temperature after cooling, and the soaking time after cooling according to different ambient temperatures, the fragmentation rate of the chemically tempered UTG glass after soaking in water can be effectively reduced, thereby improving production efficiency.
[0026] To this end, the present application provides a treatment process for chemically strengthened UTG glass, which includes: cooling the chemically strengthened UTG glass to a preset temperature, and then performing a first immersion in water at a temperature of 45 to 55° C.; wherein the first immersion time is 5 to 25 minutes.
[0027] When the ambient temperature is 0-10℃, the preset temperature is 35-60℃; when the ambient temperature is 11-20℃, the preset temperature is 38-60℃; when the ambient temperature is 21-30℃, the preset temperature is 42-60℃; when the ambient temperature is 31-40℃, the preset temperature is 47-60℃.
[0028] According to different ambient temperatures, the present application precisely controls the cooling temperature of the chemically strengthened UTG glass as well as the soaking temperature and soaking time after cooling, removes the salt bath or other chemicals that may remain on the surface of the chemically tempered UTG glass by soaking in water, promotes the release and uniform distribution of stress inside the glass, and effectively reduces the fragmentation rate of the chemically tempered UTG glass after soaking in water, thereby improving production efficiency.
[0029] The present application reduces the fragmentation rate of the chemically tempered UTG glass after soaking in water by precisely controlling the cooling temperature of the chemically strengthened UTG glass according to different ambient temperatures; as an example, when the ambient temperature is 0-10°C, the preset temperature can be any point value among 35°C, 40°C, 45°C, 50°C, 55°C and 60°C, or a range value between any two of them; when the ambient temperature is 11-20°C, the preset temperature can be any point value among 38°C, 40°C, 45°C, 50°C, 55°C and 60°C, or a range value between any two of them; when the ambient temperature is 21-30°C, the preset temperature can be any point value among 42°C, 45°C, 47°C, 50°C, 55°C and 60°C, or a range value between any two of them; when the ambient temperature is 31-40°C, the preset temperature can be any point value among 47°C, 50°C, 52°C, 55°C, 57°C and 60°C, or a range value between any two of them.
[0030] As an example, the water temperature of the first soaking after cooling can be any point value among 45°C, 47°C, 50°C, 52°C and 55°C, or a range value between any two of them; the time of the first soaking can be any point value among 5min, 10min, 15min, 20min and 25min, or a range value between any two of them.
[0031] Figure 1 For the UTG glass chemical strengthening process flow chart provided for this application, please refer to Figure 1 The treatment process of UTG glass after chemical strengthening specifically includes the following steps:
[0032] S110, cooling the chemically strengthened UTG glass to a preset temperature.
[0033] In this application, when the ambient temperature is 0-10°C, the preset temperature is 35-60°C; when the ambient temperature is 11-20°C, the preset temperature is 38-60°C; when the ambient temperature is 21-30°C, the preset temperature is 42-60°C; when the ambient temperature is 31-40°C, the preset temperature is 47-60°C.
[0034] As an example, the surface temperature of the chemically strengthened UTG glass is 120°C; when the ambient temperature is 0-10°C, the preset temperature is 35-60°C, and the cooling time is 1-5min; when the ambient temperature is 11-20°C, the preset temperature is 38-60°C, and the cooling time is 1-5min; when the ambient temperature is 21-30°C, the preset temperature is 42-60°C, and the cooling time is 1-5min; when the ambient temperature is 31-40°C, the preset temperature is 47-60°C, and the cooling time is 1-10min.
[0035] S120, the cooled UTG glass is immersed in water at a temperature of 45 to 55°C for the first time.
[0036] In some optional embodiments of the present application, the first immersion time is 15 to 25 minutes, which can further reduce the fragmentation rate of the chemically tempered UTG glass after immersion in water and improve production efficiency.
[0037] As an example, the first soaking time can be any value among 15 min, 17 min, 20 min, 22 min and 25 min, or a range value between any two of them.
[0038] S130, soaking the UTG glass after the first soaking in water with a temperature of ≤34°C for a second time.
[0039] In some optional embodiments of the present application, the second soaking time is 5 to 15 minutes.
[0040] Furthermore, the present application can further reduce the fragmentation rate of chemically tempered UTG glass after soaking in water by accurately controlling the temperature of the second soaking according to different ambient temperatures, thereby improving production efficiency.
[0041] In some optional embodiments of the present application, when the ambient temperature is 0-10° C., the temperature of the second immersion is 5-12° C.; this can further reduce the fragmentation rate of the chemically tempered UTG glass after immersion in water and improve production efficiency.
[0042] As an example, when the ambient temperature is 0-10°C, the second soaking can be any point value among 5°C, 7°C, 9°C, 10°C and 12°C or a range of values between any two of them.
[0043] In some optional embodiments of the present application, when the ambient temperature is 11-20° C., the temperature of the second immersion is 7-18° C.; this can further reduce the fragmentation rate of the chemically tempered UTG glass after immersion in water and improve production efficiency.
[0044] As an example, when the ambient temperature is 11-20° C., the second soaking can be any value among 7° C., 10° C., 12° C., 15° C. and 18° C. or a range of values between any two of them.
[0045] In some optional embodiments of the present application, when the ambient temperature is 21-30° C., the temperature of the second immersion is 16-24° C.; this can further reduce the fragmentation rate of the chemically tempered UTG glass after immersion in water and improve production efficiency.
[0046] As an example, when the ambient temperature is 21-30°C, the second soaking can be any point value among 16°C, 18°C, 20°C, 22°C and 24°C or a range value between any two of them.
[0047] In some optional embodiments of the present application, when the ambient temperature is 31-40° C., the temperature of the second immersion is 23-34° C.; this can further reduce the fragmentation rate of the chemically tempered UTG glass after immersion in water and improve production efficiency.
[0048] As an example, when the ambient temperature is 31-40° C., the second soaking can be any point value among 23° C., 25° C., 27° C., 30° C. and 34° C. or a range of values between any two of them.
[0049] The present application also provides a preparation process of UTG glass, which comprises: chemically strengthening the glass raw sheet, and then performing the treatment process after chemical strengthening of the UTG glass as provided above.
[0050] The preparation process of the UTG glass provided in the present application adopts the aforementioned treatment process for chemically strengthening the UTG glass, which can promote the release and uniform distribution of internal stress in the glass, while effectively reducing the fragmentation rate of the chemically tempered UTG glass after soaking in water, thereby improving production efficiency.
[0051] It is understandable that the treatment process of the UTG glass after chemical strengthening is consistent with the aforementioned treatment process of the UTG glass after chemical strengthening, and will not be repeated here.
[0052] In some optional embodiments of the present application, the surface temperature of the chemically strengthened UTG glass is 115-125°C.
[0053] As an example, the surface temperature of the UTG glass after chemical strengthening may be any value among 115° C., 117° C., 120° C., 122° C. and 125° C., or a range of values between any two of them.
[0054] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0055] Example 1
[0056] This embodiment provides a treatment process for UTG glass after chemical strengthening; the ambient temperature is 5°C, the glass sheet is chemically strengthened and then taken out of the furnace, and the furnace temperature is 120°C; the treatment process for UTG glass after chemical strengthening includes the following steps:
[0057] (1) The chemically strengthened UTG glass was cooled to 52°C for 5 min.
[0058] (2) The cooled glass was immersed in water at a temperature of 54° C. for a first time for 16 minutes, and then immersed in water at a temperature of 9° C. for a second time for 5 minutes to obtain UTG glass.
[0059] Example 2
[0060] This embodiment provides a treatment process for UTG glass after chemical strengthening; the ambient temperature is 15°C, the glass sheet is chemically strengthened and then taken out of the furnace, and the furnace temperature is 120°C; the treatment process for UTG glass after chemical strengthening includes the following steps:
[0061] (1) The chemically strengthened UTG glass was cooled to 54°C for 5 min.
[0062] (2) The cooled glass was immersed in water at a temperature of 53° C. for a first time for 18 minutes, and then immersed in water at a temperature of 12° C. for a second time for 7 minutes to obtain UTG glass.
[0063] Example 3
[0064] This embodiment provides a treatment process for UTG glass after chemical strengthening; the ambient temperature is 25°C, the glass sheet is chemically strengthened and then taken out of the furnace, and the furnace temperature is 120°C; the treatment process for UTG glass after chemical strengthening includes the following steps:
[0065] (1) Cool the chemically strengthened UTG glass to 58°C for 5 minutes.
[0066] (2) The cooled glass was immersed in water at a temperature of 53° C. for a first time for 18 minutes, and then immersed in water at a temperature of 21° C. for a second time for 7 minutes to obtain UTG glass.
[0067] Example 4
[0068] This embodiment provides a treatment process for UTG glass after chemical strengthening; the ambient temperature is 35°C, the glass sheet is chemically strengthened and then taken out of the furnace, and the furnace temperature is 120°C; the treatment process for UTG glass after chemical strengthening includes the following steps:
[0069] (1) Cool the chemically strengthened UTG glass to 60°C for 5 minutes.
[0070] (2) The cooled glass was immersed in water at a temperature of 53° C. for a first time for 18 minutes, and then immersed in water at a temperature of 28° C. for a second time for 7 minutes to obtain UTG glass.
[0071] Example 5
[0072] This embodiment provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 4 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0073] (1) Cool the chemically strengthened UTG glass to 50°C for 10 min.
[0074] (2) The cooled glass was immersed in water at a temperature of 52° C. for a first time for 19 minutes, and then immersed in water at a temperature of 28° C. for a second time for 8 minutes to obtain UTG glass.
[0075] Comparative Example 1
[0076] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 1 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0077] (1) The chemically strengthened UTG glass was cooled to 34°C for 10 min.
[0078] (2) The cooled glass was immersed in water at a temperature of 52° C. for a first time for 18 minutes, and then immersed in water at a temperature of 9° C. for a second time for 8 minutes to obtain UTG glass.
[0079] Comparative Example 2
[0080] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 1 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0081] (1) Cool the chemically strengthened UTG glass to 20°C for 15 minutes.
[0082] (2) The cooled glass is immersed in water at a temperature of 50° C. for a first time for 20 minutes, and then immersed in water at a temperature of 9° C. for a second time for 10 minutes to obtain UTG glass.
[0083] Comparative Example 3
[0084] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 1 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0085] (1) Cool the chemically strengthened UTG glass to 10°C for 20 minutes.
[0086] (2) The cooled glass was immersed in water at a temperature of 48° C. for a first time for 22 minutes, and then immersed in water at a temperature of 9° C. for a second time for 12 minutes to obtain UTG glass.
[0087] Comparative Example 4
[0088] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 1 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0089] (1) Cool the chemically strengthened UTG glass to 5°C for 25 minutes.
[0090] (2) The cooled glass was immersed in water at a temperature of 46° C. for a first time for 25 minutes, and then immersed in water at a temperature of 9° C. for a second time for 14 minutes to obtain UTG glass.
[0091] Comparative Example 5
[0092] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 2 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0093] (1) Cool the chemically strengthened UTG glass to 37°C for 10 min.
[0094] (2) The cooled glass was immersed in water at a temperature of 52° C. for a first time for 19 minutes, and then immersed in water at a temperature of 12° C. for a second time for 8 minutes to obtain UTG glass.
[0095] Comparative Example 6
[0096] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 2 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0097] (1) Cool the chemically strengthened UTG glass to 30°C for 15 minutes.
[0098] (2) The cooled glass was immersed in water at a temperature of 51° C. for a first time for 20 minutes, and then immersed in water at a temperature of 12° C. for a second time for 9 minutes to obtain UTG glass.
[0099] Comparative Example 7
[0100] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 2 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0101] (1) Cool the chemically strengthened UTG glass to 28°C for 20 minutes.
[0102] (2) The cooled glass was immersed in water at a temperature of 50° C. for a first time for 21 minutes, and then immersed in water at a temperature of 12° C. for a second time for 10 minutes to obtain UTG glass.
[0103] Comparative Example 8
[0104] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 2 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0105] (1) Cool the chemically strengthened UTG glass to 25°C for 25 minutes.
[0106] (2) The cooled glass was immersed in water at a temperature of 49° C. for a first time for 22 minutes, and then immersed in water at a temperature of 12° C. for a second time for 11 minutes to obtain UTG glass.
[0107] Comparative Example 9
[0108] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 2 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0109] (1) Cool the chemically strengthened UTG glass to 20°C for 30 minutes.
[0110] (2) The cooled glass was immersed in water at a temperature of 48° C. for a first time for 23 minutes, and then immersed in water at a temperature of 12° C. for a second time for 12 minutes to obtain UTG glass.
[0111] Comparative Example 10
[0112] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 2 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0113] (1) Cool the chemically strengthened UTG glass to 15°C for 35 minutes.
[0114] (2) The cooled glass was immersed in water at a temperature of 47° C. for a first time for 24 minutes, and then immersed in water at a temperature of 12° C. for a second time for 13 minutes to obtain UTG glass.
[0115] Comparative Example 11
[0116] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 3 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0117] (1) The chemically strengthened UTG glass was cooled to 41°C for 10 min.
[0118] (2) The cooled glass was immersed in water at a temperature of 52° C. for a first time for 19 minutes, and then immersed in water at a temperature of 21° C. for a second time for 8 minutes to obtain UTG glass.
[0119] Comparative Example 12
[0120] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 3 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0121] (1) The chemically strengthened UTG glass was cooled to 39°C for 15 min.
[0122] (2) The cooled glass was immersed in water at a temperature of 51° C. for a first time for 20 minutes, and then immersed in water at a temperature of 21° C. for a second time for 9 minutes to obtain UTG glass.
[0123] Comparative Example 13
[0124] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 3 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0125] (1) Cool the chemically strengthened UTG glass to 32°C for 20 min.
[0126] (2) The cooled glass was immersed in water at a temperature of 50° C. for a first time for 21 minutes, and then immersed in water at a temperature of 21° C. for a second time for 10 minutes to obtain UTG glass.
[0127] Comparative Example 14
[0128] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 3 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0129] (1) Cool the chemically strengthened UTG glass to 27°C for 25 minutes.
[0130] (2) The cooled glass was immersed in water at a temperature of 49° C. for a first time for 22 minutes, and then immersed in water at a temperature of 21° C. for a second time for 11 minutes to obtain UTG glass.
[0131] Comparative Example 15
[0132] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 3 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0133] (1) Cool the chemically strengthened UTG glass to 23°C for 30 min.
[0134] (2) The cooled glass was immersed in water at a temperature of 48° C. for a first time for 23 minutes, and then immersed in water at a temperature of 21° C. for a second time for 12 minutes to obtain UTG glass.
[0135] Comparative Example 16
[0136] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 3 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0137] (1) The chemically strengthened UTG glass was cooled to 19°C for 35 min.
[0138] (2) The cooled glass was immersed in water at a temperature of 47° C. for a first time for 24 minutes, and then immersed in water at a temperature of 21° C. for a second time for 13 minutes to obtain UTG glass.
[0139] Comparative Example 17
[0140] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 4 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0141] (1) Cool the chemically strengthened UTG glass to 45°C for 15 minutes.
[0142] (2) The cooled glass was immersed in water at a temperature of 51° C. for a first time for 20 minutes, and then immersed in water at a temperature of 28° C. for a second time for 9 minutes to obtain UTG glass.
[0143] Comparative Example 18
[0144] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 4 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0145] (1) Cool the chemically strengthened UTG glass to 40°C for 20 minutes.
[0146] (2) The cooled glass was immersed in water at a temperature of 50° C. for a first time for 21 minutes, and then immersed in water at a temperature of 28° C. for a second time for 10 minutes to obtain UTG glass.
[0147] Comparative Example 19
[0148] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 4 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0149] (1) Cool the chemically strengthened UTG glass to 35°C for 25 minutes.
[0150] (2) The cooled glass was immersed in water at a temperature of 49° C. for a first time for 22 minutes, and then immersed in water at a temperature of 28° C. for a second time for 11 minutes to obtain UTG glass.
[0151] Comparative Example 20
[0152] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 4 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0153] (1) Cool the chemically strengthened UTG glass to 30°C for 30 minutes.
[0154] (2) The cooled glass was immersed in water at a temperature of 48° C. for a first time for 23 minutes, and then immersed in water at a temperature of 28° C. for a second time for 12 minutes to obtain UTG glass.
[0155] Comparative Example 21
[0156] This comparative example provides a treatment process for UTG glass after chemical strengthening. The difference between this comparative example and Example 4 is that the treatment process for UTG glass after chemical strengthening is different. In this comparative example, the treatment process for UTG glass after chemical strengthening includes the following steps:
[0157] (1) The chemically strengthened UTG glass was cooled to 26°C for 35 min.
[0158] (2) The cooled glass was immersed in water at a temperature of 47° C. for a first time for 24 minutes, and then immersed in water at a temperature of 28° C. for a second time for 13 minutes to obtain UTG glass.
[0159] Experimental example
[0160] The yield of UTG glass obtained in Examples 1 to 5 and Comparative Examples 1 to 21 is statistically analyzed. The process differences and yield results between Example 1 and Comparative Examples 1 to 4 are shown in Table 1, the process differences and yield results between Example 2 and Comparative Examples 5 to 10 are shown in Table 2, the process differences and yield results between Example 3 and Comparative Examples 11 to 16 are shown in Table 3, and the process differences and yield results between Example 4, Example 5 and Comparative Examples 17 to 21 are shown in Table 4.
[0161] Four parallel experiments were conducted for each embodiment and comparative example. The yields in Tables 1 to 4 are the average values of the parallel experiments; yield (%) = [(M0-M1) / M0]×100%, wherein M0 is the number of UTG glasses conducted in each set of parallel experiments, and M1 is the number of UTG glasses that were broken when conducting each set of parallel experiments.
[0162] Table 1 (ambient temperature is 5°C)
[0163]
[0164]
[0165] Table 2 (ambient temperature is 15°C)
[0166]
[0167] Table 3 (ambient temperature is 25°C)
[0168]
[0169] Table 4 (ambient temperature is 35°C)
[0170]
[0171] It can be seen from Tables 1 to 4 that when the ambient temperature is different, the yield of the UTG glass after chemical tempering and soaking in water can be effectively improved by controlling the cooling temperature of the chemically strengthened UTG glass, the soaking temperature after cooling, and the soaking time after cooling.
[0172] In summary, the present application, according to different ambient temperatures, precisely controls the cooling temperature of the chemically strengthened UTG glass, the soaking temperature after cooling, and the soaking time after cooling, removes the salt bath or other chemicals that may remain on the surface of the UTG glass after chemical tempering by soaking in water, promotes the release and uniform distribution of internal stress in the glass, and effectively reduces the fragmentation rate of the UTG glass after chemically tempered soaking in water, thereby improving production efficiency.
[0173] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. A treatment process for UTG glass after chemical strengthening, characterized in that: include: The chemically strengthened UTG glass is cooled to a preset temperature and then immersed in water at a temperature of 45 to 55°C for the first time; Wherein, the first soaking time is 5 to 25 minutes; When the ambient temperature is 0-10°C, the preset temperature is 35-60°C; When the ambient temperature is 11-20°C, the preset temperature is 38-60°C; When the ambient temperature is 21-30°C, the preset temperature is 42-60°C; When the ambient temperature is 31-40°C, the preset temperature is 47-60°C.
2. The treatment process for UTG glass after chemical strengthening according to claim 1, characterized in that: The first soaking time is 15 to 25 minutes.
3. The treatment process of UTG glass after chemical strengthening according to claim 1 or 2, characterized in that: The treatment process after chemical strengthening of the UTG glass further includes: performing a second immersion on the UTG glass after the first immersion in water with a temperature of ≤34°C.
4. The treatment process for UTG glass after chemical strengthening according to claim 3, characterized in that: The second soaking time is 5 to 15 minutes.
5. The treatment process for UTG glass after chemical strengthening according to claim 3, characterized in that: When the ambient temperature is 0-10°C, the temperature of the second soaking is 5-12°C.
6. The treatment process for UTG glass after chemical strengthening according to claim 3, characterized in that: When the ambient temperature is 11-20°C, the temperature of the second soaking is 7-18°C.
7. The treatment process for UTG glass after chemical strengthening according to claim 3, characterized in that: When the ambient temperature is 21-30°C, the temperature of the second soaking is 16-24°C.
8. The treatment process for UTG glass after chemical strengthening according to claim 3, characterized in that: When the ambient temperature is 31-40°C, the temperature of the second immersion is 23-34°C.
9. A process for preparing UTG glass, characterized in that: include: The glass raw sheet is chemically strengthened, and then subjected to the post-chemical strengthening treatment process of the UTG glass according to any one of claims 1 to 8.
10. The process for preparing UTG glass according to claim 9, characterized in that: The surface temperature of the chemically strengthened UTG glass is 115-125°C.